Low‐Lanthanide‐Content CeO2/MgO Catalysts with Outstandingly Stable Oxygen Storage Capacities: An In‐Depth Structural Characterization by Advanced STEM Techniques1. Issue 22 (5th November 2015) - Tinoco, Miguel; Sanchez, Juan J.; Yeste, María P.; Lopez‐Haro, Miguel; Trasobares, Susana; Hungria, Ana B.; Bayle‐Guillemaud, Pascale; Blanco, Ginesa; Pintado, José M.; Calvino, José J.
Abstract: A novel CeO2 /MgO catalyst with low ceria loading has been synthesized. This catalyst showed unique redox properties compared with conventional high and low surface area CeO2 . Advanced (scanning) transmission electron microscopy techniques revealed the presence of a variety of highly dispersed ceria nanostructures: isolated CeO x entities, CeO2 clusters, as well as fairly small (<5 nm) CeO2 nanoparticles. More interestingly, this CeO2 /MgO catalyst showed outstanding stability in its redox response against high temperature aging treatments. Thus, after reduction in hydrogen at 950 °C and further oxidation at 500 °C, CeO2 reduction effects took still place at low temperatures, and no significant loss of oxygen storage capacity (OSC) was detected. Unique ceria‐bilayer nanostructures were found and characterized in the aged catalyst. Their peculiar structural and chemical properties seem to be responsible for the large improvement observed in the stability of the redox response. Abstract : Outstanding CeO x : Thanks to a detailed and advanced transmission electron microscopy characterization, a complete understanding of the outstanding redox properties of CeO2 /MgO catalysts was achieved. The samples possess unprecedented CeO x structures that make them unique and very promising materials to substitute current ceria‐based catalysts.